Психолого-педагогічний потенціал фізичної культури і спорту у вихованні навичок лідерства студентів вищих навчальних закладів - Тіняков, Артем Олександрович (НТУ ХПІ", 2016)
У статті аналізуються можливості та шляхи реалізації психолого-педагогічного потенціалу фізичної культури і спорту у вихованні лідерства студентів вищих навчальних закладів. Середовище фізичної культури і спорту має величезний виховний потенціал, а лідерство є одним із головних ознак фізкультурно-спортивної діяльності. У статті проаналізовано процес фізичного виховання і занять спортом у вищих навчальних закладах з позиції впливу на розкриття лідерського потенціалу, формування лідерських здібностей та навичок студентів. Конкретизовано лідерські навички, що формуються у студентів під час фізичного виховання і занять спортом та необхідні для цього організаційно-педагогічні умови.

The article analyzes the realization of the psychological and pedagogical potential of physical culture and sport in the education of the leadership of university students. Among physical culture and sports has great educational potential, and leadership is one of the main features of sports activity. Common psychological and pedagogical features of sports activity in leadership development are mechanisms desire to win, self-improvement and self-realization. To do this, leadership functions are reduced to the ability to lead to the achievement of this goal, the inclusion of mechanisms for the social and psychological impact on other team members, the impact on the group activity and the impact on others in choosing the direction and the nature of their activities. In the process of physical education and sport formed specialized leadership skills to inspire others the idea and deed; show constant and undying activity in the pursuit of individual and team success; to be able to distribute the roles within the team and or ganize the effective interaction between all members of the team, taking into account their strengths and weaknesses; be prepared to take responsibility for their results, and the team result; to be able to operate effectively in extreme situations; maintain a high level of motivation in the fight for the leadership; be able to quickly convey thoughts and management decisions to others. In article also given organizational guidelines for the construction of the process of physical education in higher educational institutions from the perspective of the impact of the disclosure of leadership potential, the formation of leadership abilities and skills of students
Psycho-pedagogical potential of physical education and sport in education of leadership skills University students
Keywords: фізкультурно-спортивна діяльність; виховання лідерства; педагогічні технології; лідерські задатки; лідерські здібності; leadership education; leadership inclinations; leadership abilities; leadership skills